The blue economy handbook of the Indian ocean region - Attri, Vishva Nath; Bohler-Mulleris, Narnia (Africa Institute of South Africa, 2018)
As humanity enters the Anthropocene epoch the oceans are more at risk than ever before as a result of the increased exploitation of its resources. The Indian Ocean is the third largest ocean in the world comprising 20% of the water on the Earth's surface. The sea lanes in the Indian Ocean are among the busiest in the world with more than 80 percent of global seaborne trade in oil transiting through the Indian Ocean and its vital chokepoints and an estimated 40% of the world's offshore oil production comes from the Indian Ocean. The importance of this region cannot be underestimated and there is no doubt that there are many opportunities for economic growth and job creation presented by the waters washing the shores of the Indian Ocean Rim. In order to ensure a desirable future for humanity it is necessary to make use of the ocean's resources in a sustainable and responsible manner. Climate change is affecting the Indian Ocean negatively, placing a strain on the ability to ensure food security and damaging the economies of small island states that depend on fisheries and aquaculture for their livelihoods. Increasing ocean temperatures and ocean acidification are taking a toll on ecosystems. This book is the first of its kind, providing fresh insights into the various aspects and impacts of the Blue Economy in the Indian Ocean Region: from shifting paradigms, to an accounting framework, gender dynamics, the law of the sea and renewable energy, this handbook aims at increasing awareness of the Blue Economy in the Indian Ocean Region and to provide evidence to policy-makers in the region to make informed decisions. The contributions are from a mixture of disciplines by scholars and experts from seven countries.